Fuzzy Information and Engineering Volume 1 - Cao, Bingyuan; Zhang, Cheng-Yi; Li, Tai-Fu (Advances in Intelligent and Soft Computing,, 2009)
This book is the proceedings of the Third Annual Conference on Fuzzy Information and Engineering (ACFIE2008) from Dec. 5-10, 2008 in Haikou, China. The Third Annual Conference on Fuzzy Information and Engineering (ACFIE2008), built on the success of previous conferences, the ACFIE2005 (Guangzhou, China), is a major symposium for scientists, engineers and practitioners in China to present their updated results, ideas, developments and applications in all areas of fuzzy information and engineering. It aims to strengthen relations between industry research laboratories and universities, and to create a primary symposium for world scientists. Each of the papers chosen from the 155 submissions has undergone a rigorous review process. Only high-quality papers in fuzzy fields are included such as: Fuzzy intelligence, neural networks and optimal; Fuzzy algebra; Fuzzy analysis; Fuzzy systems and logic; Fuzzy topology and measure; Fuzzy probability, control, forecasting and decision-making; Fuzzy clustering and fuzzy algorithms; Application in fuzzy sets; Rough sets and its application; etc.